Algebraic informatics : 8th International Conference, CAI 2019, Niš, Serbia, June 30-July 4, 2019, Proceedings /: 8th International Conference, CAI 2019, Niš, Serbia, June 30-July 4, 2019, Proceedings. (2019) - Unknown
No abstract available